Perjanjian Pagang Gadai Tanah di Nagari Gunung Padang Alai Kecamatan V Koto Timur Kabupaten Padang Pariaman - Firdaus, Ahmad; Nurdin, Zefrizal; Yasniwati, Yasniwati (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The pawn agreement for high-ranking land in West Sumatra is commonly known as pawn, which was originally a form of mutual assistance in society but has since transformed into an economic and/or capitalist transaction. Based on this, the author formulates the following problems: 1. The Process of Forming a Pawn Agreement in Nagari Gunung Padang Alai, V Koto Timur District, Padang Pariaman Regency. 2. What are the causes of disputes and how are land pawn agreements resolved? This research method is empirical juridical research, meaning research conducted on the real conditions of society or the community environment with the intent and purpose of finding facts, which then leads to identifying problems and ultimately leading to solving related problems and connecting them with the reality of the land pawn agreement in Nagari Gunung Padang Alai, Padang Pariaman Regency. The results of this study indicate that 1. Pagang gadai pusako tinggi carried out by the pawnbroker and the pawnbroker for the object to be pawned must be through an agreement between the two parties and witnessed by several people who are considered to maintain the sanctity of the agreement, one of which is pawnbroking as raising the tarandam stem, such as the lack of funds to continue the education of children of clan members, resulting in pawnbroking of the clan's pusako land. 2. The causes of disputes and disagreements are resolved according to customary law regulations or resolved in the District Court. Customary law regulations are also referred to as Customary Civil Procedure Law or customary formal civil law. In deliberation and consensus, they will always adhere to the elements that exist and develop within the community environment. These elements are better known as Tali sapilin tigo, which includes elements of religion, custom, and law.